Contributory factors of the Pension 65 program and its relationship with the well-being of the elderly - Calderon-Chipana, Juan C. (2022)
Aging leads to the physical and mental deterioration of the person, it is a stage of maximum fragility, so the presence of social assistance programs that promote a decent stay at this stage is dispensable. For this reason, the Pension 65 program emerges, whose purpose is to ensure the well-being of the elderly living in poverty. Therefore, the objective of the research was to determine the contributory factors of the Pension 65 program and its relationship with the well-being of the elderly in the district of Pilcuyo, province of El Collao. The study was framed within the quantitative approach of the correlational type, non-experimental design. The sample consisted of 196 elderly beneficiaries. The results showed that there is a relationship between: household targeting (r=0.903**) and affiliation criteria, non-contributory pension (r=0.875**) and access to basic services, and between social assistance (r=0.890* *) and social satisfaction. In conclusion, the contributory factors of Pension 65 are significantly related (+0.891**, p<0.05) with the well-being of the elderly.